The knowledge and opinions of maternity wards patients in Kielce on the patient rights - Wrześniewska, Marzena; Adamczyk-Gruszka, Olga; Gruszka, Jakub; Komar-Gruszka, Karolina; Bąk, Beata (Journal of Education, Health and Sport, 2017)
Introduction: A legal and ethical obligation of a midwife is to inform patients about their rights in the course of therapeutic and nursing care and to respect these rights in practice. Aim of the research: The goal of the research was to determine patient’s rights awareness among obstetric patients as well as sources from which this knowledge came. After taking into account the state of knowledge about the patient’s rights based on opinions of respondents, their feelings related to a stay in a hospital were identified. Material and methods: The research was conducted in a group of 161 patients of maternity hospitals in Kielce. The research material was obtained by the author and anonymous questionnaire. The results were subjected to statistical analysis by a test chi^2 (c2). Results: In the group of sample women, more than half (52.8%) did not know the patient's rights. Some of them (41%) said that they have heard of those rights but cannot name any of them. 47.2% of the respondents mentioned by at least one right. The primary source of information about the patient's rights are TV and radio (43.7%). The midwife ranks last position among the available sources of information about the patient's rights. For the patients who know better their rights the midwife is often a source of information about them (19.7%) than for those who claimed that they have only heard about them, but they cannot name any of them (7.6%). The majority of the rights (4-5 <5) were mentioned by the 12 (15.8%) patients, who in addition to the Internet 9 (75%), a significant source of information indicated the midwife 8 (66.7%). Among women who did not know the patient's rights, more than half (65.9%) identified their stay in the maternity ward as not stressful, but among those who demonstrated a better understanding of the rights half (52.6%) constituted women who their stay in the hospital identified as stressful events. Conclusions: A level of the knowledge of the patient’s rights among the sample women is insufficient. The vast majority of the respondents learned about the patient’s rights in other way than that connected with the activities of the midwife. The most common are: TV, radio, the Internet, magazines. A level of information about the patient’s rights measured by a number of the said rights is better in case of the patients whose knowledge came from the midwife. Patients who know what their rights are, expect a professional medical care - based on patients rights, if there is not like that, they describe their staying in hospital as stressful.